Experimentally controlled study indicates that the naturally occurring recombinant vaccine-like lumpy skin disease strain Udmurtiya/2019, detected during freezing winter in northern latitudes, is transmitted via indirect contact - Nesterov, Alexander; Mazloum, Ali; Byadovskaya, Olga; Shumilova, Irina; Van Schalkwyk, Antoinette; Krotova, Alena; Kirpichenko, Vladimir; Donnik, Irina; Chvala, Ilya; Sprygin, Alexander (Frontiers in Veterinary Science, 2022)
Lumpy skin disease (LSD) caused by LSD virus (LSDV), is a member of the poxvirus genus Capripoxvirus. It is classified as a notifiable disease by the World Organization for Animal Health (OIE) based on its potential for rapid spread and global economic impact. Due to these characteristics, the mode of LSDV transmission has prompted intensive research efforts. Previous experimental studies using the virulent vaccine-derived recombinant LSDV strain Saratov/2017, demonstrated that this strain has the capacity for transmission in a vector-proof environment. This study demonstrated that a second novel recombinant vaccine-derived LSDV strain Udmurtiya/2019, can infect bulls in-contact with diseased animals, in the absence of insect vectors. Bulls were housed in an insect proof animal biosafety level 3 facility, where half the animals were inoculated intravenously with the recombinant LSDV (Udmurtiya/2019), whilst the remaining five animals were mock-inoculated but kept in contact with the inoculated group. Both the infected / inoculated group (IN) and uninfected / incontact group (IC), were monitored for 41 days with continuous registration of body temperature, observations for clinical signs and collection of blood samples and nose swabs for testing of LSDV presence using real-time PCR. Results indicated that cohabitation of animals from both groups was sufficient to transmit the virus from the IN to the IC-group, with the onset of clinical signs including pyrexia ( 41°C) and classical LSD nodular skin lesions starting at 10 dpi for the IN group and 16 dpi for the IC-group. Additionally, the presence of LSDV genomes as well as anti-LSDV antibodies were detected in swabs, blood and serum samples from animals belonging to both groups. This provides experimental evidence for an alternative in-contact method of transmitting recombinant LSDVs. Additionally it demonstrates that recombination-driven genetic alterations exert a profound impact on LSDV, conferring or even unlocking unknown features in novel mosaic strains of LSDV.